Reconceptualizing Integrity Crisis Management in State-Owned Enterprises: A Multi-Stakeholder Perspective on the 2025 Fuel Adulteration Scandal - Aulia, Gita Cahya; Arsitatri, Zachwa Maulani Salsabilla; Fitri, Nurul Aprilia; Ananda, Muhammad Rifqy; Subrata, Pramudya Ibnu (The Indonesian Institute of Science and Technology Research, 2026)
This research explores the critical shift in crisis communication management within State-Owned Enterprises (SOEs), focusing on PT Pertamina (Persero) during the 2025 fuel contamination crisis. The study aims to bridge the gap between Situational Crisis Communication Theory (SCCT) and the unique socio-political burdens faced by state entities by proposing a new framework, the